(untitled) (World Science, 2022)
Many urban areas face pressure from growing populations, limited resources and environmental impacts. Cities need sustainable architecture and sustainable construction. The green cover of Sevlievo (Bulgaria) is 27.49%. Defined as a sustainable town by a number of authors, in 2012 was built a park system on the territory of the old barracks. The park has the following types of value - environmental, economic and social. Increasing the resilience of urban architecture requires improving materials. Since there are buildings and houses and since there are builders and architects. Construction involves maintaining a number of balances: balance between form and function; between design aspirations and financial constraints and between artistic expression (as manifested in the works of architects) and the practical care of the construction sector. This is where the concept of sustainable development responds to the needs of the present, without compromising the capabilities of future generations.